Does school physical education really contribute to accelerometer-measured daily physical activity and non sedentary behaviour in high school students? - Mayorga-Vega, Daniel; Martínez-Baena, Alejandro; Viciana-Ramírez, Jesus (Taylor & Francis, 2018)
Physical education has been highlighted as an important environment for physical activity promotion, however, to our knowledge there are no previous studies examining the contribution of physical education to daily accelerometer-measured physical activity and non sedentary behaviour. The purpose was to compare the accelerometer-measured physical activity and sedentary behaviour between physical education, non-physical education and weekend days in adolescents. Of the 394 students from a Spanish high school that were invited to participate, 158 students (83 boys and 75 girls) aged 13-16 years were analyzed (wear time ≥ 600 min). Participants’ physical activity and sedentary behaviour were objectively-measured by GT3X+ accelerometers during physical education (one session), non-physical education and weekend days. Results indicated that overall adolescents had statistically significant greater physical activity levels and lower values of sedentary behaviour on physical education days than on non-physical education and weekend days (e.g., moderate-to-vigorous physical activity = 71, 54 and 57 min; sedentary = 710, 740 and 723 min) (p < 0.05). Physical education contributes significantly to reducing students’ daily physical inactivity and sedentary behaviour. Increasing the number of physical education classes seems to be an effective strategy to reduce the high current prevalence of physical inactivity and sedentary behaviour in adolescence.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/5753?template=romeo
Keywords: Ejercicio físico - Adolescentes; Educación física para adolescentes; PE; Moderate-to-vigorous physical activity; Objectively-measured physical activity; Accelerometry; Adolescents